Can Multimodal Pain Management in TKA Eliminate Patient-controlled Analgesia and Femoral Nerve Blocks?. Issue 1 (January 2018) - Yu, Stephen; Dundon, John; Solovyova, Olga; Bosco, Joseph; Iorio, Richard
Abstract: Background: TKA pain management protocols vary widely with no current consensus on a standardized pain management regimen. Multimodal TKA pain management protocols aim to address pain control, facilitate functional recovery, and maintain patient satisfaction. Questions/purposes: (1) Did changes to our pain management protocol, specifically adding liposomal bupivacaine, eliminating patient-controlled analgesia (PCA), and discontinuing femoral nerve blocks (FNBs), affect narcotic consumption after TKA? (2) Did these changes to our pain management protocols affect patient-reported pain scores? (3) Does the use of an immediate postoperative PCA affect rapid rehabilitation and functional recovery? (4) How did changes to our pain management regimen affect discharge disposition and pain-related Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) scores? Methods: We retrospectively analyzed an institutional arthroplasty database between September 2013 and September 2015 containing 1808 patients who underwent primary TKA. Departmental pain management protocols were compared in 6-month periods as the protocol changed. All patients received a multimodal pain management protocol including preoperative oral medications, spinal or general anesthesia, a short-acting intraoperative pericapsular injection, and continued postoperative oral narcotics for breakthrough pain. From September 2013 to April 2014, all patients received an intraoperative FNB and a PCA for the first 24 hours postoperatively (Cohort 1). From May 2014 to October 2014, a periarticular injection of liposomal bupivacaine was added to the protocol and FNBs were discontinued (Cohort 2). After April 2015, PCA was eliminated (Cohort 3). No other major changes were made to the TKA pain management pathways. Narcotic use, pain scores on 8-hour intervals, physical therapy milestones, and discharge disposition were compared. Results: Total narcotic use was the least in Cohort 3 (Cohort 3: 66 ± 54 morphine milligram equivalents versus Cohort 2: 82 ± 72 versus Cohort 1: 96 ± 62; p < 0.001). There was an increase in pain score immediately after surgery in Cohort 3 (4.0 ± 3.5 versus 1.2 ± 2.2 versus 1.2 ± 2.5, post hoc analysis of Cohort 2 versus 3: mean difference 2.6, 95% confidence interval [CI] 2.2-3.0; p < 0.001); however, it was not different for the remainder of the hospital stay. Patients who did not receive PCA reached functional milestones for both gait and stairs faster by postoperative day 1 (47% [328 of 698] versus 30% [158 of 527] versus 16% [93 of 583], p < 0.001; Cohort 3 versus 2: odds ratio 2.1, 95% CI 1.6-2.6; p < 0.001). Discharge to home occurred more frequently (84% [583 of 698] versus 78% [410 of 527] versus 72% [421 of 583], p = 0.010) in Cohort 3. There were no differences in pain-related HCAHPS scores across all cohorts. Conclusions: Discontinuing PCAs and FNBs from our multimodal TKA pain management protocols and adding liposomal bupivacaine resulted in fewer narcotics consumed with no difference in pain control and faster functional recovery while maintaining high HCAHPS scores relating to pain. Level of Evidence: Level III, therapeutic study.